Penggunaan Lafaz Bahjah, Jamal dan Zukhruf dalam Al-Qur’an (TAFSE: Journal of Qur'anic Studies, 2020)
The choice of vocabulary in the Qur'an is not a coincidence, but each word has its own value of balaghah. The beauty of the language and style of the Qur'an can be seen from its balaghah and fasahah, both concretely and abstractly. The Qur'an sometimes uses several words that have the same or close meanings, so there seems to be an inconsistency in the words it uses. This study will examine the use of the words bahjah, jamᾱl and zukhruf which means beautiful in the Qur'an. This research is library research using the maudhu'i method. The main sources of data are the verses of the Qur'an that contain the words bahjah, jamᾱl and zukhruf as well as secondary sources in the form of books of tafsir, mu'jam and other related scientific sources. In the Qur'an, the words bahjah, jamᾱl and zukhruf have meanings that are almost related to each other but with different contexts and purposes. Bahjah is defined by the beautiful colors used to express the beauty in the trees, flowers, mountains, oceans, etc. that make the earth look beautiful. Jamᾱl in the Qur'an is generally used to describe the beauty that radiates from a nature that will not be mentioned unless there is dispute or friction. As for zukhruf, it is used in the Qur'an to mention concrete decoration, but if it is paired with other words, then the decoration in question is abstract decoration. Pemilihan kosa kata dalam Alquran, bukanlah suatu kebetulan tetapi setiap kata mempunyai nilai balaghah tersendiri. Keindahan bahasa dan uslub Alquran yang menakjubkan terlihat dari balaghah dan fasahahnya, baik yang konkrit maupun abstrak. Alquran kadangkala menggunakan beberapa kata yang memiliki arti sama atau dekat, sehingga tampak adanya inkonsistensi dalam kata-kata yang digunakannya. Kajian ini akan mengkaji penggunaan lafaz bahjah, jamᾱl dan zukhruf  yang bermakna indah dalam Alquran. Penelitian ini berupa riset kepustakaan (library research) dengan menggunakan metode maudhu’i. Sumber data utama yaitu ayat-ayat Alquran yang mengandung lafaz bahjah, jamᾱl dan zukhruf serta sumber sekunder berupa kitab-kitab tafsir, mu’jam dan sumber ilmiah terkait lainnya. Dalam Alquran lafaz bahjah, jamᾱl dan zukhruf  mempunyai makna yang hampir berkaitan antara satu dengan lainnya namun dengan konteks dan tujuan yang berbeda. Bahjah diartikan dengan warna yang indah yang  digunakan untuk menyebutkan keindahan pada pepohonan, bunga-bungaan, pegunungan, lautan, dan lain-lain yang menjadikan bumi terlihat indah. Jamᾱl dalam Alquran pada umumnya digunakan untuk menyebutkan keindahan yang terpancar dari sesuatu sifat yang tidak akan disebutkan kecuali terjadi perselisihan atau gesekan. Adapun zukhruf digunakan dalam Alquran untuk menyebutkan hiasan yang konkrit akan tetapi jika disandingkan dengan kata lain maka hiasan yang dimaksud adalah hiasan yang abstrak.
Keywords: Muradif; Bahjah; Jamal; Zukhruf